Remoção de sementes por formigas, aves e roedores em área de Cerrado e seu efeito sobre o recrutamento de plântulas - Ferreira, Alana Vaz (2008)
Many plant populations are affected by seed consumers since these can affect the rates and patterns of seedling recruitment. Ants, birds and rodents are main agents of seed removal. Therefore, the aim of this study was to determine the relative importance of ants, birds and rodents on seed removal in different types of Cerrado vegetations and to determine the effects of seed removal on seedling recruitment. Field work was performed at Panga Ecological Station near Uberlândia, MG, Brazil, in the foolowing vegetation types: cerrado sensu stricto, cerrado denso e cerradão. I determined the seed removal rates for the following tree species: Coussarea hydrangeaefolia, Guapira graciliflora, Maprounea guianensis, Matayba guianensis, Siparuna guianensis e Virola sebifera. Seeds were placed in three types of stations, one with access for ants only, one with access to ants and rodents and with access to ants, rodents and birds. In each station I placed 20 seeds of each species that were left in place for 96h. Seed removal rates varied little among the three types of vegetation. Maprounea guianensi was the species with the greatest removal rate: 97,4%. Of the seeds removed for ants were 10 more than birds and rodents. To determine the effects of seed removal on seedling recruitment I built a series of exclosures (each 70 x 70 cm), and compared seedling recruitment (both for planted seeds of Guapira graciliflora and for existing seeds of all dicot species) between predator exclosures and control plots. There were significantly more seedlings of Guapira graciliflora in the exclosure than in control plots. Also, 8 months after removal of seed consumers, I detected a significantly greater rate of natural seedling emergence in the exclosure plots.